2006
DOI: 10.1542/peds.2006-1218
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of the Epidemiology of SporadicSalmonellaInfection in Infants

Abstract: We identified a number of modifiable protective and risk factors for salmonellosis in infants. Attention should be directed at developing effective preventive measures for this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
5

Year Published

2009
2009
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 27 publications
5
79
0
5
Order By: Relevance
“…Previous epidemiological studies identified riding in shopping carts near meat or poultry products as an associated risk factor in infant Salmonellosis and Campylobacteriosis. 40,41 Contamination of shopping carts and baskets handles could be ascribed to their frequent use by shoppers.…”
Section: Figurementioning
confidence: 99%
“…Previous epidemiological studies identified riding in shopping carts near meat or poultry products as an associated risk factor in infant Salmonellosis and Campylobacteriosis. 40,41 Contamination of shopping carts and baskets handles could be ascribed to their frequent use by shoppers.…”
Section: Figurementioning
confidence: 99%
“…Because international travel can itself be an important risk factor for enteric disease, the risk associated with travel can be examined by including patients reporting international travel before illness (EberhartPhillips et al, 1997;Kassenborg et al, 2004b;Stafford et al, 2006). Specific age groups were studied in 11 studies (14%); four studies focused on infants (Tenkate and Stafford, 2002;Rowe et al, 2004;Jones et al, 2006b;Fullerton et al, 2007).…”
Section: Case Definitionmentioning
confidence: 99%
“…Over half of the studies reported the number of eligible case-patients excluded (54%), while less than 15% of studies reported the number of potential controls excluded. Flow diagrams were used to illustrate the study population in some of the studies (Varma et al, , 2007Jones et al, 2006b;Voetsch et al, 2007;Denno 2009), and their value has been recognized in the reporting of randomized controlled trials (Egger et al, 2001). …”
Section: Case Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular children are at a higher risk from this transmission route, given their behaviors (close proximity with pets, petting zoos, more likely to put hands in their mouth, etc.) and developing immune systems [16,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%